Determination of Polyphenol Oxidase Activity during Rooting in Cutting of Some Grape Varieties (Vitis vinifera L.) - COBAN, HARUN (Asian Journal of Chemistry, 2010)
Poly phenol oxidase (PPO) activity was investigated during rooting in cuttings from six grape cultivars (Vitis vinifera L. cvs. Sultana, round seedless, Yalova incisi, Trakya ilkeren, Pembe Gemre and Cardinal) and the enzyme activity and rooting ability were compared. Rooting was observed on Sultana, round seedless, Yalova incisi and Trakya ilkeren cuttings, but not on the pembe gemre and cardinal cuttings. PPO activity started to increase in the early stage of the experiment and decreased after root emergence in the Sultana, round seedless, Yalova incisi and Trakya ilkeren cuttings. However, enzyme activity started to increase in the early stages and continued throughout the experiment in the pembe gemre and cardinal cuttings. In concluded that PPO does not any effect on the after formation of the root. However, it is found that PPO affects cell division, cell differentiation and the development of root primordial considerably.